Un/ethical Company and Brand Perceptions: Conceptualising and Operationalising Consumer Meanings - Brunk, Katja H. (2012)
Based on three empirical studies, this research sets out to conceptualise and subsequently operationalise the construct of consumer perceived ethicality (CPE) of a company or brand. Study 1 investigates consumer meanings of the term ethical and reveals that, contrary to philosophical scholars’ exclusively consequentialist or nonconsequentialist positions, consumers’ ethical judgments are a function of both these evaluation principles, illustrating that not any one scholarly definition of ethics alone is capable of capturing the content domain. The resulting conceptualisation identifies six key themes explicating the construct. Building upon these findings, studies 2 and 3 were conducted to operationalise CPE. Such operationalisation is an essential prerequisite for future explorations and theory development given the absence of a suitable tool to capture and quantify the strength and direction of CPE. The key focus was on developing a valid and reliable multi-item measurement tool that is practical, parsimonious and easy to administer. The scale’s general applicability allows deployment in academic and business contexts as well as different research areas and doing thus facilitates the much-needed theory building in this new research area.
Keywords: Scale Development; Construct conceptualisation; Brand perceptions; Consumer perceived ethicality (CPE); Corporate social responsibility (CSR); Consumer meanings; corporate ethics